Post-Infectious Acute Cerebellar Ataxia Treatment, a Case Report and Review of Literature - Emanuela Del Giudice; Filippo Mondì; Greta Rachele Bazzanella; Alessia Marcellino; Vanessa Martucci; Giovanna Pontrelli; Mariateresa Sanseviero; Piero Pavone; Silvia Bloise; Salvatore Martellucci; Anna Carraro; Flavia Ventriglia; et al. (MDPI AG, 2023)
Background: infectious mononucleosis is very common during childhood and neurological manifestations are extremely rare. However, when they occur, an appropriate treatment must be undertaken to reduce morbidity and mortality as well as to ensure appropriate management. Methods: we describe the clinical and neurological records of a female patient with post-EBV acute cerebellar ataxia, whose symptoms rapidly resolved with intravenous immunoglobulin therapy. Afterwards, we compared our results with published data. Results: we reported the case of an adolescent female with a 5-day history of sudden asthenia, vomiting, dizziness, and dehydration, with a positive monospot test and hypertransaminasemia. In the following days, she developed acute ataxia, drowsiness, vertigo, and nystagmus with a positive EBV IgM titer, confirming acute infectious mononucleosis. The patient was clinically diagnosed with EBV-associated acute cerebellitis. A brain MRI showed no acute changes and a CT scan showed hepatosplenomegaly. She started therapy with acyclovir and dexamethasone. After a few days, because of her condition's deterioration, she received intravenous immunoglobulin and demonstrated a good clinical response. Conclusions: although there are no consensus guidelines for the treatment of post-infectious acute cerebellar ataxia, early intervention with intravenous immunoglobulin might prevent adverse outcomes, especially in cases that do not respond to high-dose steroid therapy.